1982
DOI: 10.1063/1.555660
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Properties of Aqueous Sodium Chloride Solutions

Abstract: Literature data for the volumetric properties of sodium chloride solutions to concentrations of 5.5 molal have been compiled and critically evaluated. A semi-empirical equation of the same type found to be effective in describing the thermal properties of NaCl solutions has been used to reproduce the volumetric data from O °C to 300 °C and 1 bar to 1000 bar. Tables of values are given for the specific volume, expansivity, and compressibility. Equations also are given for calculating the pressure dependence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
210
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 319 publications
(228 citation statements)
references
References 8 publications
17
210
1
Order By: Relevance
“…The approach used to estimate the uncertainty in isothermal compressibility of seawater, given in Appendix A, could not be used for isobaric expansivity as expansivity was not found to vary linearly with salinity. This non-linearity was verified by analyzing data on the isobaric expansivity of aqueous sodium chloride reported by Rogers and Pitzer [45] for a wide range of temperature, salinities, and pressures (0 ≤ t ≤ 300 °C; 0 ≤ S ≤ 226 g/kg; 0.1 ≤ P ≤ 100 MPa) and, by analyzing seawater data reported by Safarov et al [5]. The only alternative we saw to obtain an upper bound on the uncertainty in this range (S > 56 g/kg) was by comparing values obtained from the correlation for isobaric expansivity of seawater developed in this work, given in Eq.…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 4 more Smart Citations
“…The approach used to estimate the uncertainty in isothermal compressibility of seawater, given in Appendix A, could not be used for isobaric expansivity as expansivity was not found to vary linearly with salinity. This non-linearity was verified by analyzing data on the isobaric expansivity of aqueous sodium chloride reported by Rogers and Pitzer [45] for a wide range of temperature, salinities, and pressures (0 ≤ t ≤ 300 °C; 0 ≤ S ≤ 226 g/kg; 0.1 ≤ P ≤ 100 MPa) and, by analyzing seawater data reported by Safarov et al [5]. The only alternative we saw to obtain an upper bound on the uncertainty in this range (S > 56 g/kg) was by comparing values obtained from the correlation for isobaric expansivity of seawater developed in this work, given in Eq.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Analysis of isobaric expansivity data of aqueous sodium chloride from Rogers and Pitzer [45] showed that expansivity did not vary strictly linearly with salinity, especially at low temperature (< 20 °C).…”
Section: Isobaric Thermal Expansivitymentioning
confidence: 99%
See 3 more Smart Citations